Characterization of Mineralocorticoid Receptor Antagonist Therapy Initiation in High-Risk Patients With Heart Failure. (January 2017) - Cooper, Lauren B.; Hammill, Bradley G.; Peterson, Eric D.; Pitt, Bertram; Maciejewski, Matthew L.; Curtis, Lesley H.; Hernandez, Adrian F.
Abstract : Background—: Heart failure guidelines recommend routine monitoring of serum potassium, and renal function in patients treated with a mineralocorticoid receptor antagonist (MRA). How these recommendations are implemented in high-risk patients or according to setting of drug initiation is poorly characterized. Methods and Results—: We conducted a retrospective cohort study of Medicare beneficiaries linked to laboratory data in 10 states with prevalent heart failure as of July 1, 2011, and incident MRA use between May 1 and September 30, 2011. Outcomes included laboratory testing before MRA initiation and in the early (days 1–10) and extended (days 11–90) post-initiation periods, based on setting of drug initiation and the presence of renal insufficiency. Additional outcomes included abnormal laboratory results and adverse events proximate to MRA initiation. Of 10 443 Medicare beneficiaries with heart failure started on an MRA, 19.7% were initiated during a hospitalization. Appropriate follow-up laboratory testing across all time periods occurred in 25.2% of patients with inpatient initiation compared with 2.8% of patients begun as an outpatient. Patients with chronic kidney disease had higher rates of both hyperkalemia and acute kidney failure in the early (1.3% and 2.7%, respectively) and extended (5.6% and 9.8%, respectively) post-initiation periods compared with those without chronic kidney disease. Conclusions—: Patients initiated on MRA therapy as an outpatient had extremely poor rates of guideline indicated follow-up laboratory monitoring after drug initiation. In particular, patients with chronic kidney disease are at high risk for adverse events after MRA initiation. Quality improvement initiatives focused on systems to improve appropriate laboratory monitoring are needed. Abstract : Supplemental Digital Content is available in the text.